EP1002 Secondary cytoreduction surgery for recurrent ovarian cancer – twelve radiological criteria for case selection: preliminary data. (1st November 2019) - Tsahalina, E; Sohaib, A; Mcaddy, N; Bryan, S; Nobbenhuis, M; Ind, T; Butler, J; Barton, D
Abstract : Introduction/Background: Aim: To identify 12 radiological criteria predictors of complete secondary cytoreductive surgery to assist case selection. Methodology: This is a retrospective review of all recurrent cases of ovarian, fallopian tube and peritoneal cancer that have undergone secondary cytoreductive surgery (SCS) with the goal of complete cytoreduction from January 2013 till December 2017 in a single institution. Preoperative imaging (CT scans) were available for all patients. Patients with bowel obstruction, Krukenberg tumours and those with imaging older than 2 months prior to surgery were excluded. A consultant Radiologist who have the responsibility for multidisciplinary meetings (Tumour Boards) has reviewed the images and scored the presence or absence of 12 radiological criteria preoperatively for all cases. The Radiologist was blind to surgical outcome. Operation reports of all patients were reviewed. Results: 83 patients met the above criteria and were included in the study. In 57 complete cytoreduction was achieved (69%). In 26 patients with incomplete cytoreduction the following radiological criteria according to the scoring were present and influenced the outcome: diffuse non-measurable disease (N=15), subcapsular liver lesions (N=12), omentum involvement (N=11) with extension to the lesser sac (superior body of pancreas-inferior stomach antrum) (N=7), other sites of disease (N=22). Causes for incomplete surgery identified intraoperatively and included: extensive carcinomatosis with wide spread small volume disease, infiltrating plaque-like disease on the upper or lower abdomen with multi-visceral involvement, tumour invading right/left pelvic side wall (including iliac vessels), tumour involving sacral/bladder wall, or small bowel mesentery. Conclusion: In most cases imaging studies were in accordance with the operating findings. However, further cases are required to validate these 12 radiological criteria, for patients selection, in whom secondary cytoreductive surgery is considered. Disclosure: Nothing to disclose.